Management of Maternity with Back Pain Discomfort at the Clinic: Tatalaksana Ibu Bersalin Dengan Ketidaknyamanan Nyeri Punggung di Klinik - Hidayah, Widya Awwalul; Cholifah, Cholifah; Rosyidah, Rafhani (Universitas Muhammadiyah Sidoarjo, 2020)
Relaxation techniques are one of the natural techniques used to treat pain, especially during childbirth. The purpose of this study was to determine the difference between mothers who used breathing or relaxation techniques. The population of this study was all mothers born at BPM Nuril Masrukah Candi Sidoarjo, 2020. Data were collected through interviews with patients. The results of the data examination showed that the active phase I labor pain was 4-10 cm. During the first stage and the second stage, the labor pain did not occur normally, so the man whiney test was used to analyze it. The results of the study showed that the difference in the meaning of labor pain at the time of complete opening was 4-10cm (0.016), while the difference in the meaning of labor pain in the first stage was 0.001, while the study found that the difference was not significant (in the treatment group and the control group, birth pain radiated to the back at an opening more than 4-10 cm). The results showed that relaxation techniques can reduce labor pain radiating to the back and the length of labor in the first stage of the active phase.